On Fredholm-Type Integral Equations in Topological Hölder Spaces. (27th July 2021) - Temizer Ersoy, Merve; Furkan, Hasan
Abstract: Using the technique associated with the classical Schauder fixed point theorem we demonstrate the existence of solutions of a class of quadratic integral equation of Fredholm type in Hölder spaces. Moreover, one useful example is discussed to justify our theoretical results.